Forest Institutions in Transition : Experiences and Lessons from Eastern Europe - World Bank (Washington, DC, 2021)
The overall context for the study is partly provided by the three pillars of the World Bank's new forest strategy (Sustaining Forests: A Development Strategy, 2002), which focuses on how the Bank can most effectively contribute to harnessing the potential of forests to reduce poverty, to integrating forests in sustainable economic development, and to protecting global forest values. How institutions perform is central to the ability to deliver on this agenda. Consistent with the Strategy, the aim of this study is to provide an overview of forest sector organizations and reform processes within Europe's transition economies and to provide strategic guidance on institutional performance criteria for meeting the objective of multi-functional and environmentally sustainable forest management. The authors draw on experiences from other countries - largely from within the OECD or which are otherwise 'forest rich' - to provide examples of the range of institutional forms and structures for forest management. Also considered are some of the special challenges for countries which are moving toward accession to the European Community (EC) as they seek to develop their forest management institutions in a manner which is perceived to be broadly consistent with other EC models and standards. What emerges in this review is that there is a need for forest organizations to define with greater clarity the performance standard against which organizational reforms are to be assessed. The authors propose an agenda for reform which focuses on the transforming of forest organizations into service delivery institutions.